Pengaruh Jenis Ikan dan Metode Pemasakan terhadap Mutu Abon Ikan - Chairil - Anwar (Universitas Sriwijaya, 2018)
Fish is one source of animal protein that is widely consumed by society, is easy to get, and the price is cheap. But fish quickly experience the process of decay. Therefore, fish preservation should be known to all levels of society. One of the products of fish processing through the process of preservation is abon. Abon fish is a type of preserved food made from fish that are seasoned, processed by boiling, frying and pressing or separating oil. The resulting product has a soft shape, good taste, distinctive smell, and has a long-lasting power. This study aims to examine the effect of fish species and the method of cooking fish meat is the steaming and boiling treatment of the quality of fish produced abon. The results showed that fish species had a significant effect (P ? 0,01) on protein content, moisture content, fat content, ash content and color organoleptic value, and not significant (P> 0,05) to yield, the organoleptic value of texture, aroma, and flavor. The method of cooking fish meat was very significant (P ? 0,01) to protein content, fat content and not significant (P> 0,05) to yield, water content, ash content, the organoleptic value of texture, aroma, color, and flavor. The interaction between fish species and cooking method of fish meat had no significant effect (P> 0,05) on all parameters except on yield of abon fish produced.